2015
DOI: 10.1007/s10278-015-9820-6
|View full text |Cite
|
Sign up to set email alerts
|

Online Error Reporting for Managing Quality Control Within Radiology

Abstract: Information technology systems within health care, such as picture archiving and communication system (PACS) in radiology, can have a positive impact on production but can also risk compromising quality. The widespread use of PACS has removed the previous feedback loop between radiologists and technologists. Instead of direct communication of quality discrepancies found for an examination, the radiologist submitted a paper-based quality-control report. A web-based issue-reporting tool can help restore some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Consistently, previous studies managed to increase reporting rates when the reporting was anonymous and performed on web-bases systems. 11,12,15 An evaluation of the rates of the reported errors showed that medication errors were the most frequently reported events. The types and frequencies of medication errors indicated that dosage calculation errors were common The complicated calculations of small dosages for children increase the occurrence rates of these errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, previous studies managed to increase reporting rates when the reporting was anonymous and performed on web-bases systems. 11,12,15 An evaluation of the rates of the reported errors showed that medication errors were the most frequently reported events. The types and frequencies of medication errors indicated that dosage calculation errors were common The complicated calculations of small dosages for children increase the occurrence rates of these errors.…”
Section: Discussionmentioning
confidence: 99%
“…10 The relevant literature focuses on the importance of anonymous reporting systems that are addressed to increasing the number of reports by eliminating barriers that interfere with reporting errors by health professionals. 11 Examination of various web-based reporting systems developed around the world shows that there are specific reporting systems such as anonymous, web-based standardized monitoring techniques 12 and medication error reporting systems, 13 Electronic Clinic Safety Reporting System, which are developed for hospitals. 14 Users enter texts about what happens during the reporting, which are not configured, as well as the classified and coded structures of data.…”
Section: Introductionmentioning
confidence: 99%
“…Golnari et al [7] conducted a study in which they assessed the impact of point-of-care feedback by purchasing and implementing a commercially available tool, also similarly integrated with the PACS in a multifacility radiology department. In that study, the issue submission rate was 0.25% of overall examination volume compared with 0.6% in our data.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of the commercially available tool was also not reported. Cost comparisons can readily be made by obtaining quotes from that vendor [7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation